Diabetes Knowledge and Self-care Practice in Type II Diabetic Patients: An Immigrant Population-based Study. - Leila, Alizadeh; Leili, Salehi (Journal of Diabetes Nursing (2345-5020), 2018)
Introduction: The global prevalence of diabetes is expected to increase. Diabetes knowledge and self-care practice are the most important factors in diabetes management. This study aimed to investigate the diabetes knowledge and self-care practice in relation to glucose control in patients with type II diabetes mellitus. In the Shahryar city took place in 2016. Materials and Methods: This cross-sectional study was conducted on 450 patients with type II diabetes mellitus referring to the diabetes clinic of Shahriar city, Tehran, Iran, in 2016. The subjects were selected through simple random sampling methods. The data were collected using demographic characteristic form, Tobert-Glacow selfcare scale, and diabetic knowledge questionnaire. The inclusion criteria were a minimum of one year history of diabetes. Data analysis was performed in SPSS software using descriptive and analytic statistical tests (i.e., t-test, ANOVA, Pearson correlation test, and logistic regression analysis). Results: The mean age of the participants was 50±14.65, and 42.4% of the subjects were male. The data analysis revealed no significant difference between the males and females in terms of diabetes knowledge and self-care practice. The majority of the participants had moderate level of diabetes knowledge and self-care practice. Dietary self-care and blood glucose monitoring were the most important factors predicting diabetic control. Conclusion: As the findings of the study indicated, the provision of the diabetic patients with appropriate dietary and glucose monitoring training are of significant importance to control the disease.